Педагогические условия развития профессионального самоопределения старшеклассников в процессе внеурочной деятельности - Турмухамедова, Э.Ж.; Беленко, О.Г.; Мукатаева, А.К. (My University, 2016)
The paper deals with the process of professional self-determination of senior pupils. The authors point to the need for specific teaching conditions in career guidance of high school students with the aim of building an effective professional self-determination and reveal the influence of thinking type of senior pupils as an intra factor for professional orientation.
Keywords: Pedagogical conditions; professional orientation; professional self-determination; orientation; type of thinking,; profile training; professional self-determination of pre training; vocational guidance work; the quality of education